Epidemiology of Diarrhea in Two Major Cities in Saudi Arabia - Milaat, Waleed Abdullah; Elassouli, Sufian Mohamad (Paediatrica Indonesiana, 2018)
The epidemiological pattern of diarrheal diseases, causative agents, and risk factors of their occurrence in two referral hospital of Saudi Arabia was investigated in this study. Stool specimens from 1726 admitted diarrheal cases were examined for parasites, yeast, enteropathogenic bacteria and rotavirus using the ELISA test. Two-fifth of cases were due to rotavirus (RVGE) while 53.1% of cases showed no causative pathogens. Mean age of all cases was 20.2 months and RVGE cases showed a steady rise from the neonatal period onward, reaching a peak between 6-14 months. Males were of higher percentage in diarrheal cases. Mothers of diarrhea cases were mostly house wives with low educational level. Bottle fed children showed higher proportion {53.1 %) of diarrhea than other types of feeding suggesting the feco-oral route of infection and the effect of poor sanitation. A pattern of higher RVGE cases was seen in warmer months in Al-taif and in cooler months in Jeddah. Our findings demonstrated the interaction between host, pathogen and environmental factors m the epidemiology of infectious diarrhea in developing countries and the areas of possible prevention.